2014
DOI: 10.7732/kjpr.2014.27.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Infection Effects with AMF (Arbuscular-Mycorrhizal Fungi) Isolated from Upland Plants

Abstract: This study was carried out to investigate the characteristics and infection effects of AMF with soil samples collected at some sites in Gyeonggi province, Korea. AMF spore and characteristics of infection structure in upland plant root were observed as wet sieving and staining method, growth of Capsicicum annum was compared between treatment and non treatment. AMF spores isolated from each soil sample were ellipse or circle type and the colors were soft yellow and white. The colonization rate of AMF with soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In particular, organic fertilizer may promote AMF root colonization by enhancing AMF spore germination and growth rates. Organic fertilization elevates AMF abundance and shapes the community, which may facilitate symbiosis between AMFs and plants [51]. The presence of mycorrhiza may favor plant nutrient acquisition by speeding up the transformation of organic manure [52].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, organic fertilizer may promote AMF root colonization by enhancing AMF spore germination and growth rates. Organic fertilization elevates AMF abundance and shapes the community, which may facilitate symbiosis between AMFs and plants [51]. The presence of mycorrhiza may favor plant nutrient acquisition by speeding up the transformation of organic manure [52].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of researchers have begun to explore the mechanisms behind the ecological restoration of degraded grassland in terms of soil microbial diversity, community structure, and functions. The findings indicated that (i) the restoration of degraded grassland was closely related to microbial activities, and (ii) the application of organic fertilizer changed the species composition, structure, richness, and diversity of bacterial and fungal communities in the soil [ 24 ], (iii) facilitated the enrichment of beneficial microorganisms [ 25 ] and (iv) strengthened the colonization of arbuscular mycorrhizal fungi, a significant symbiotic microbial group in the soil, to gramineous plants [ 26 ]. Furthermore, the grass–legume mixture increased the plant yield while enhancing the stability and complexity of the rhizosphere soil bacterial community network.…”
Section: Introductionmentioning
confidence: 99%